Niereligijni rodzice wobec instytucji szkoły - Sylwester Zielka (Problemy Wczesnej Edukacji)
The purpose of the paper is to identify and analyse problems reported by non-religious parents. These parents are subjects of the education process whose children attend Polish educational (usually public) institutions, in which religion is one of the elements of the curriculum. The study is guided by the assumption that such a situation may lead to various tensions and conflicts, the expression of which can be found on the Internet as a space for communication and search for solutions. The research presented in this paper is of an exploratory nature. It includes content analysis of posts posted on one of the Facebook social networking groups. Analysed statements of non-religious parents indicate that pre-schools and primary schools are to a large extent institutions strongly connected with declared religious values, which also leads to a negative perception of non-religious parents and their children.